GaN-Based Cascade Micro Light-Emitting Diode in Parallel and Series Arrays for Visible Light Communication - Shihao Liang; Guobin Wang; Tao Tao; Feifan Xu; Kai Chen; Ting Zhi; Zhifang Zhu; Wenjuan Chen; Yong Li; Ke Xu; Bin Liu; Rong Zhang (IEEE Photonics Journal)
GaN-based micro light-emitting diode (LED) has gradually become one of the promising light sources for visible light communication (VLC), of which high modulation bandwidth has been demonstrated. In order to acquire high speed and high brightness for VLC application, the modulation bandwidth and optical performance of micro-LEDs were investigated in series and parallel in this work. The electrical characteristics, optical characteristics and communication characteristics of single-pixel, 2-pixel, 4-pixel series and parallel green micro-LEDs with different pixel sizes were systematically tested. High modulation bandwidth as much as 1.4 GHz was acquired by using 10 μm micro-LEDs with 4-pixel in parallel. It is found that parallel micro-LED array can achieve higher modulation bandwidth, higher brightness and higher stability as well, which can be used as the preferred mode for the development of micro-LED based VLC.